1995
DOI: 10.1016/0092-8674(95)90356-9
|View full text |Cite
|
Sign up to set email alerts
|

An amino-terminal domain of Mxi1 mediates anti-myc oncogenic activity and interacts with a homolog of the Yeast Transcriptional Repressor SIN3

Abstract: Documented interactions among members of the Myc superfamily support a yin-yang model for the regulation of Myc-responsive genes in which transactivation-competent Myc-Max heterodimers are opposed by repressive Mxi1-Max or Mad-Max complexes. Analysis of mouse mxi1 has led to the identification of two mxi1 transcript forms possessing open reading frames that differ in their capacity to encode a short amino-terminal alpha-helical domain. The presence of this segment dramatically augments the suppressive potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
360
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 369 publications
(368 citation statements)
references
References 42 publications
8
360
0
Order By: Relevance
“…REFs were transfected with expression constructs of c-myc, H-RAS G12v , mTERT, and pBABE vector control according to Figure 5, by the calcium phosphate method as described (Schreiber-Agus et al, 1995). Plates were split 1 to 3 at 20 h after transfection and media was changed every 3 days.…”
Section: Rat Embryo ®Broblast Cooperation Assaymentioning
confidence: 99%
“…REFs were transfected with expression constructs of c-myc, H-RAS G12v , mTERT, and pBABE vector control according to Figure 5, by the calcium phosphate method as described (Schreiber-Agus et al, 1995). Plates were split 1 to 3 at 20 h after transfection and media was changed every 3 days.…”
Section: Rat Embryo ®Broblast Cooperation Assaymentioning
confidence: 99%
“…Indeed SMRT and N-CoR interact strongly with unliganded receptors and are released upon ligand binding. A series of recent reports (Alland et al, 1997;Hassig et al, 1997;Heinzel et al, 1997;Kadosh and Struhl, 1997;Laherty et al, 1997;Zhang et al, 1997) have shown that SMRT/ N-CoR co-repressors are part of a multiprotein complex including the Mad co-repressors mSin3A and B (Ayer et al, 1995;Schreiber-Agus et al, 1995) and the histone deacetylases HDAC1/HD1 and HDAC2/mRPD3 (Taunton et al, 1996;Yang et al, 1996). These studies, that strengthen the major role of histone acetylation/deacetylation in transcriptional regulation, provide the basis for the existence of a common repression pathway between nuclear receptors and basic region-helix ± loop ± helix-leucine zipper (bHLH-Zip) proteins.…”
Section: Introductionmentioning
confidence: 99%
“…N-CoR and its close homologue SMRT were cloned as co-repressors of the thyroidhormone and retinoic acid receptors (Chen and Evans, 1995;Horlein et al, 1995). Both N-CoR and SMRT have been shown to be components of large protein complexes that include histone deacetylase (Taunton et al, 1996; Nagy et al, 1997) and Sin3 (Ayer et al, 1995;Schreiber et al, 1995). Moreover, N-CoR is involved in Mad repression, reviewed by (Schreiber and DePinho, 1998).…”
Section: Introductionmentioning
confidence: 99%